2014
DOI: 10.1007/s40618-014-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy syndrome in HIV treatment-multiexperienced patients: implication of resistin

Abstract: In our young HIV-positive population, LD had high prevalence with predominance of LA subtype. LA was associated with high resistin levels and greater number of ARV regimens in overall group and female subgroup. Resistin could be used as a marker of peripheral adipose tissue loss and might be used as a target for new anti-LD therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…For instance, a mixed phenotype of HIV-positive patients comprising illicit drug and alcohol use, and anti-retroviral treatment-experienced individuals exhibit lower and upper trunk adipose depots (45) , chronic cannabis smoking is associated with lower abdominal subcutaneous adiposity (46) , cigarette smoking is associated with higher visceral adiposity (47) , while cathinone, the active compound in khat, induces lipolysis in vivo and inhibit free fatty release in isolated adipocytes (48) . Although NRTIs induce increased development of lipodystrophic syndromes in HIV patients (49, 50) , none of our patients exhibited features of lipodystrophy. Therefore, serum adiponectin is a useful surrogate indicator of altered visceral and subcutaneous adiposity in IDUs on anti-retroviral treatment.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…For instance, a mixed phenotype of HIV-positive patients comprising illicit drug and alcohol use, and anti-retroviral treatment-experienced individuals exhibit lower and upper trunk adipose depots (45) , chronic cannabis smoking is associated with lower abdominal subcutaneous adiposity (46) , cigarette smoking is associated with higher visceral adiposity (47) , while cathinone, the active compound in khat, induces lipolysis in vivo and inhibit free fatty release in isolated adipocytes (48) . Although NRTIs induce increased development of lipodystrophic syndromes in HIV patients (49, 50) , none of our patients exhibited features of lipodystrophy. Therefore, serum adiponectin is a useful surrogate indicator of altered visceral and subcutaneous adiposity in IDUs on anti-retroviral treatment.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, the positive associations of waist perimeter and adiponectin, are partly, similar to previous studies showing increased fatty liver in individuals with higher waist girth previously observed among HCV infected non-alcoholic patients (53) . Abnormal central fat accumulation is a manifestation of HIV-associated lypodystrophy in patients on anti-retroviral treatment (49, 50) . However, central and visceral adiposity in HIV and HCV co-infected treatment-naive and HCV mono-infected IDUs indicates alterations in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…While higher circulating levels of resistin have been implicated in the development of IR 29 and diabetes, 30 its role in HIVLD is inconclusive. Some cross-sectional studies have reported an increase in circulating resistin levels in HIVLD patients, 31 while other studies failed to find an association 32 or even reported a reduction in resistin levels. 33 We observed a significant reduction in the amount of resistin secreted by the adipocyte with all PIs including ATV although the ATV effect was comparatively less than those of other PIs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, greater plasma resistin levels were observed in HIV patients compared with uninfected controls [42]. However, other workers have found no association between serum resistin and fat redistribution, and metabolic profile in HIV-infected patients [43,44]. The physiological role of resistin, therefore, is not fully understood and needs further studies.…”
Section: Discussionmentioning
confidence: 94%